Muslim Youth Readiness for Indonesia Emas 2045 in the Era of Disruption: Digital and Islamic Economic Literacy, Islamic Values, and Organizational Participation - Mawaddatul Ulya; Asmi Lidya Pradipta Rahayu; Taufik Taufik; Ratih Ayu Muflihah (Madania: Jurnal Kajian Keislaman, 2026)
This study analyzes the readiness of Indonesian Muslim youth to support the Indonesia Emas 2045 vision. Readiness is invoked constantly in debates about Indonesia’s demographic bonus, yet it is rarely defined in terms that can be measured. This study operationalizes the readiness of Indonesian Muslim youth through four indicators, namely digital literacy, Islamic economic literacy, internalization of Islamic values, and participation in Islamic organizations, and examines how far each contributes to youth awareness of the Indonesia Emas 2045 vision. A quantitative survey was administered to 100 Muslim youth respondents selected by purposive sampling from varied educational and organizational backgrounds across several regions of Indonesia. The instrument used a five-point Likert scale and was tested for validity and reliability, followed by classical assumption testing and multiple linear regression processed in SPSS. Participation in Islamic organizations emerged as the strongest predictor (β = 0.283; t = 3.292; p = 0.001), followed by digital literacy (β = 0.218; t = 2.193; p = 0.031). Islamic economic literacy (p = 0.164) and Islamic values (p = 0.136) were positive but not significant at the partial level. The four indicators were jointly significant, F (4, 95) = 51.224, p < 0.001, and explained 67% of the variance in awareness (adjusted R² = 0.670). The findings indicate that readiness is not a single undifferentiated capacity but a division of function: organizational involvement and digital competence act as direct channels, whereas economic literacy and religious values operate as an enabling moral and cognitive foundation that requires a practical arena before it turns into national awareness. Strengthening spaces for collective participation therefore matters as much as strengthening individual literacy. Penelitian ini menganalisis kesiapan pemuda Muslim Indonesia dalam menghadapi era disrupsi menuju terwujudnya Indonesia Emas 2045. Kesiapan merupakan istilah yang terus disebut dalam perdebatan mengenai bonus demografi Indonesia, tetapi jarang dirumuskan dalam ukuran yang dapat diuji. Penelitian ini mengoperasionalkan kesiapan pemuda Muslim Indonesia melalui empat indikator, yaitu literasi digital, literasi ekonomi syariah, internalisasi nilai-nilai Islam, dan partisipasi dalam organisasi Islam, serta menguji sejauh mana masing-masing berkontribusi terhadap kesadaran pemuda akan visi Indonesia Emas 2045. Survei kuantitatif dilakukan terhadap 100 responden pemuda Muslim yang dipilih secara purposive dari beragam latar belakang pendidikan dan organisasi di sejumlah wilayah Indonesia. Instrumen menggunakan skala Likert lima poin dan diuji validitas serta reliabilitasnya, dilanjutkan uji asumsi klasik dan regresi linear berganda melalui SPSS. Partisipasi dalam organisasi Islam merupakan prediktor terkuat (β = 0,283; t = 3,292; p = 0,001), diikuti literasi digital (β = 0,218; t = 2,193; p = 0,031). Literasi ekonomi syariah (p = 0,164) dan nilai-nilai Islam (p = 0,136) berpengaruh positif namun tidak signifikan secara parsial. Keempat indikator signifikan secara simultan, F(4; 95) = 51,224; p < 0,001, dan menjelaskan 67% variasi kesadaran (adjusted R² = 0,670). Temuan ini menunjukkan bahwa kesiapan bukan kapasitas tunggal yang seragam, melainkan pembagian fungsi: keterlibatan organisasi dan kompetensi digital bekerja sebagai jalur langsung, sementara literasi ekonomi dan nilai keagamaan berfungsi sebagai landasan moral dan kognitif yang memerlukan wadah praktis sebelum berubah menjadi kesadaran kebangsaan. Penguatan ruang partisipasi kolektif karena itu sama pentingnya dengan penguatan literasi individual.